X-rays induced alterations in mechanical and biochemical properties of isolated SH-SY5Y nuclei - Andolfi, Laura; Meschini, Roberta; Filippi, Silvia; Bedolla, Diana E.; Piccirilli, Federica; Lepore, Maria; Delfino, Ines (Biochimica et biophysica acta. General subjects, 2023)
The use of ionizing radiations in radiotherapy is an effective and very common cancer treatment after surgery. Although ionizing-radiation DNA damages are extensively investigated, little is known about their effects on the other nuclear components, since their variations when studied in whole cells can be difficult to decouple from those of the cytoplasmatic structures. The organization of nuclear components plays a functional role since they are directly involved in some of the nuclear response to chemical or physical stimuli. For this reason, studying the X-ray effects on nuclear components is a crucial step in radiobiology. We have used Atomic Force Microscopy (AFM) and micro-FTIR to examine the biomechanical and biochemical properties of hydrated fixed nuclei isolated from neuroblastoma (SH-SY5Y) cells irradiated by 2, 4, 6 and 8 Gy X-ray doses. The experimental results have shown that, already at 2 Gy irradiation dose, the nuclei exhibit not only a DNA damage, but also relevant alterations of lipid saturation, protein secondary structure arrangement and a significant decrease in nuclear stiffness, which indicate a remarkable chromatin decondensation. The present work demonstrates that a multi-technique approach, able to disclose multiple features, can be helpful to achieve a comprehensive picture of the X-ray irradiation effects of the nuclear components and distinguish them from those occurring at the level of cytoplasm. [Display omitted] •The study of X-ray effects on nuclear components is a crucial step in radiobiology.•Isolated nuclei from irradiated neuroblastoma cells are studied by AFM and micro-FTIR.•Micro-FTIR evidences DNA damages, changes in lipid saturation and protein secondary structure.•X-ray radiation effects on nuclear stiffness are observed by AFM.•Our approach gives multiple information on X-ray effects on nuclear components.